The Dark Side of Efficiency: The Unexpected Impact of AI on Social Cohesiveness and Work Culture in the Modern Office Environment - Nandini Aquila Lukito; Nazwa Sabila (Asosiasi Ahli Administrasi Indonesia, 2026)
Artificial Intelligence (AI) significantly transforms contemporary workplaces by improving efficiency and production. Nonetheless, its implementation also incurs unforeseen social and ethical ramifications. This study investigates the efficiency paradox of AI, emphasizing the impact of technical optimization on human values, social cohesiveness, and workplace culture. A qualitative literature assessment of studies from 2020 to 2025 delineates four principal themes: efficiency and automation, algorithmic bias, alteration of professional identity, and social interaction. Research indicates that AI can lead to dehumanization, deskilling, and diminished interpersonal communication, whereas algorithmic governance may exacerbate bias and inequality within businesses. These factors undermine trust and communal involvement. The study indicates that the ethical and human-centric integration of AI is crucial to ensure that efficiency gains align with inclusivity, justice, and the maintenance of social well-being in contemporary workplaces.